The Research of Primary School Second Stage Students' Parents' Attitudes Related to Course of Physical Education According to Their Education Levels - Rıdvan Kır; Sinan Ayan (Türk Spor ve Egzersiz Dergisi)
In this study the relationship between educational levels of primary school second stage students' parents and their attitudes related to Course of Physical Education and Sports was analysed. The samples were randomly chosen from 7 primary schools; 389 female and 384 male students attended voluntarily. For measuring the attitudes of children, “the scale of Primary school second stage students' attitudes related to Course of Physical Education” was used. The scale consists of two sections. The first section consists of 12 items about personal information and the second section consists of 20 items with the type of 5 point likert scale about the attitudes related to Course of Physical Education. Firstly, the frequency distribution of the data was measured within descriptive statistics and crosstab values were examined. In the study, correlation analysis was made between the 3 factors created by factor analysis (interest to the course, attitude to the teacher, course hour) and the education level of the children's parents. For the paired comparison in independent samples, t-test and one-way analysis of variance-ANOVA were carried out. For the significant difference at the results of one-way ANOVA analysis, Post-Hoc test was used for designating which group caused this difference. Meaningful differences were observed between the parents' education levels and the attitudes of them related to Course of Physical Education and between the students' interests to Course of Physical Education and the attitudes related to course hour.